2013
DOI: 10.5688/ajpe77231
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Application of Knowledge From the Classroom to Introductory Pharmacy Practice Experiences

Abstract: Objective. To determine whether and how pharmacy students used knowledge learned in the classroom during their introductory pharmacy practice experiences (IPPEs) in community and hospital settings. Design. To reinforce course concepts and make connections between coursework and practice, students documented examples of how knowledge from first-year courses was used in IPPEs. Assessment. Data submitted were categorized by classroom-based pharmacy course, including the frequency with which each course was cited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Students have notable contributions in providing patient care during their experiential learning, which in turn will provide benefits to both patients and training site (Turner et al, 2000). Community pharmacy is a good area for pharmacy students to practice what they learn in pharmacy school (Krueger, 2013). In Saudi Arabia, there were 8114 private pharmacy which employed a total of 14,935 pharmacists in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Students have notable contributions in providing patient care during their experiential learning, which in turn will provide benefits to both patients and training site (Turner et al, 2000). Community pharmacy is a good area for pharmacy students to practice what they learn in pharmacy school (Krueger, 2013). In Saudi Arabia, there were 8114 private pharmacy which employed a total of 14,935 pharmacists in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the knowledge-based assessments were basics of asthma treatment, and clearly indicate the need for more comprehensive training of pharmacy students. This is particularly important, now that pharmacy practice is playing an increasingly greater role in healthcare, especially through the introduction of specialized ward pharmacy services in hospitals [8].…”
Section: Discussionmentioning
confidence: 99%
“…As pharmaceutical care is patient-centred, pharmacists can encourage patients to be involved with self-management, consequently improving their adherence to long-term medication therapies [17]. In a study conducted at the University of Wyoming School of Pharmacy to show pharmacy students' application of their knowledge from the classroom to introductory pharmacy practice experiences, it was concluded that challenging students to think about and provide specific examples of knowledge application made the connections more explicit and also allowed students to see the relevance of the classroom portion of their education and reinforced how foundational course concepts are directly applicable to pharmacy practice [8].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practicums are considered essential to professional competence in most health-based professions. For example, clinical practicums are viewed as essential to the curriculum by programs in medicine (Ruesseler & Obertacke, 2011), nursing (Courtney- Pratt et al, 2011), pharmacy (Krueger, 2013), physical therapy (Buccieri et al, 2013;McCallum et al, 2013), occupational therapy (Rodger et al, 2011), dietetics (Dietitians of Canada, n.d.), radiation therapy (Leaver, 2012), paramedic training (McCall et al, 2009, and dental hygiene (Paulis, 2011). Internationally, clinical practicum placements for students in these and other health-care disciplines are in markedly short supply.…”
Section: Pic T U R E Of T H E CL I N Ic a L L E A R N I Ng E N V I Ron M E N Tmentioning
confidence: 99%